Retained bullets and lead toxicity: a systematic review. (3rd October 2022) - Kershner, Emily K.; Tobarran, Natasha; Chambers, Andrew; Wills, Brandon K.; Cumpston, Kirk L.
Abstract: Introduction: Lead toxicity secondary to retained bullet(s) (RB) after a penetrating gunshot wound is a rare but likely underdiagnosed condition, given the substantial number of firearm injuries in the United States. There is currently no consensus on the indications for surveillance, chelation, or surgical intervention. Objective: The purpose of our review is to summarize the literature on systemic lead toxicity secondary to RBs to help guide clinicians in the management of these patients. Methodology: The primary literature search was conducted in Medline (PubMed), EMBASE, Cochrane, and CENTRAL using the following MESH terms: "chelation" and "lead poisoning" or "lead toxicity" or "lead" and "bullet" or "missile" or "gunshot", or "bullet". Results: The search identified 1, 082 articles. After exclusions, a total of 142 articles were included in our final review, the majority of which were case reports. Several factors appear to increase the risk of developing lead toxicity including the location of the RB, the presence of a fracture or recent trauma, number of fragments, hypermetabolic states, and bullet retention duration. Particularly, RBs located within a body fluid compartment like an intra-articular space appear to be at a substantially higher risk of developing lead toxicity. Even though patients with lead toxicity from RBs will have similar symptoms to patients with lead toxicity from other sources, the diagnosis of lead poisoning may occur months or years after a gunshot wound. Symptomatic patients with high blood lead levels (BLLs) tended to improve with a combination of chelation and surgical removal of RBs. Conclusions: We suggest surveillance with serial BLLs should be performed. Patients with intra-articular RBs appear to be at increased risk of lead toxicity and if possible, early surgical removal of the RBs is warranted, especially given that signs of toxicity are vague, and patients may not have access to follow-up. Long-term chelation should not be used as a surgical alternative and management should be multidisciplinary.